PKM Penelitian Tindakan Kelas (PTK) - M. Yusuf A. Ngamapo; Nuraisyiah Nuraisyiah; Zulfikar Yusuf Yusuf (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Partners of the Community Partnership Program (CPP) are UPT SMK 7 Takalar. The problem are (1) partners do not study learning problems that occur in class, and (2) partners do not accustom to studying learning problems yet in class in the form of classroom action research (CAR). The methodsare tolecture, question and answer, simulation, and practice. The results achieved are (1) partners can study learning problems that occur in class, and (2) partners can solve learning problems in the form of classroom action research (CAR).